Increasing Warmth in Adolescents with Anorexia Nervosa: A Randomized Controlled Crossover Trial Examining the Efficacy of Mustard and Ginger Footbaths. (31st January 2020) - Kuderer, S.; Helmert, E.; Szöke, H.; Joos, S.; Kohl, M.; Svaldi, J.; Beissner, F.; Andrasik, F.; Vagedes, J.
Abstract : Objective . To analyze the thermogenic effects of footbaths with medicinal powders in adolescents with anorexia nervosa (AN) in comparison to healthy controls (HCs). Intervention and Outcomes . Forty-one female participants (21 AN, 20 HCs; 14.22 ± 1.54 years) received three footbaths—warm water and mustard (MU, Sinapis nigra), warm water and ginger (GI, Zingiber officinale), or warm water only (WA), in random order within a crossover design. Data were collected before (t1), immediately after foot immersion (maximum 20 minutes) (t2), and after 10 minutes subsequently (t3). Actual skin temperature (high resolution thermography) and perceived warmth (HeWEF questionnaire) were assessed at each time point for various body parts. The primary outcome measure was self-perceived warmth at the feet at t3. Secondary outcome measures were objective skin temperature and subjective warmth at the face, hands, and feet. Results . Perceived warmth at the feet at t3 was significantly higher after GI compared to WA (mean difference −1.02) and MU (−1.07), with no differences between those with AN and HC (−0.29). For the secondary outcome measures, a craniocaudal temperature gradient for the skin temperature (thermography) was noted at t1 for patients with AN and HC (AN with colder feet). The craniocaudal gradient for subjective warmth was only seen for patients with AN. Conclusion . Footbaths with ginger increased warmth perception at the feet longer than with mustard or warm water only for adolescents with AN as well as for HC. The impact of ginger footbaths on recovery of thermoregulatory disturbances in patients with AN repeated over extended periods merits further investigation.